They would mostly be interested in accounting
Answer:
−15x2+23x−6
Step-by-step explanation:
(3x−1)(−5x+6)
=(3x+−1)(−5x+6)
=(3x)(−5x)+(3x)(6)+(−1)(−5x)+(−1)(6)
=−15x2+18x+5x−6
=−15x2+23x−6
There are no solutions to this problem,
Let's solve your equation step-by-step.
3
x
+
1
=
3
x
Step 1: Subtract 3x from both sides.
3
x
+
1
−
3
x
=
3
x
−
3
x
1
=
0
Step 2: Subtract 1 from both sides.
1
−
1
=
0
−
1
0
=
−
1
There are no solutions
Answer:
A. Rational number
Step-by-step explanation:
It is not a whole number or integer because it's a fraction. so it's the rational of a whole number.